Pursuing Equity in and Through Teacher Education Program Admissions - Childs, Ruth; Broad, Kathryn; Gallagher-Mackay, Kelly; Sher, Yael; Escayg, Kerry-Ann; McGrath, Christopher (Education Policy Analysis Archives, 2011)
This case study investigated equity in teacher education admissions. Through document analysis and structured interviews with ten past or current members of the admissions committee in a large initial teacher education program in Ontario, we developed an understanding of equity in teacher education admissions as encompassing two foci: equity in admissions—that is, equity of access for applicants to the program—and equity through admissions—that is, equity of educational opportunity and outcomes for the children in the schools where the teachers trained by the programs will eventually teach. Our analysis illustrates the importance of recognizing both foci and the tensions between them